2013
DOI: 10.1155/2013/723432
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Growth Hormone-Producing Pituitary Adenomas in 242 Acromegaly Patients: Classification according to Hormone Production and Cytokeratin Distribution

Abstract: The aim of this study was to clarify the relationship between the histological features of GH-producing adenomas surgically resected at the Toranomon Hospital and the clinical features of the patients. Histological examinations, including immunohistochemistry for anterior pituitary hormones and cytokeratin (CK), were performed on 242 consecutively excised GH-producing pituitary adenomas. Immunohistochemistry showed 45% of the adenomas to be monohormonal and 55% to be plurihormonal, producing GH-PRL (77%), GH-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
8
19
3
1
Order By: Relevance
“…Compared to previously published literature, in our cohort there was no difference in age, gender or tumor volume between two different GH tumors subtype patients likely due to our smaller sample size (Bakhtiar et al, 2010,Mazal et al, 2001,Kiseljak-Vassiliades et al, 2014,Bando et al, 1992,Obari et al, 2008,Mori, Inoshita, Takahashi-Fujigasaki et al, 2013). The response to surgery was dramatically different in patients with DG compared to SG growth hormone tumors similar to prior reports (Bakhtiar et al, 2010,Mazal et al, 2001,Kiseljak-Vassiliades et al, 2014).…”
Section: Discussioncontrasting
confidence: 79%
“…Compared to previously published literature, in our cohort there was no difference in age, gender or tumor volume between two different GH tumors subtype patients likely due to our smaller sample size (Bakhtiar et al, 2010,Mazal et al, 2001,Kiseljak-Vassiliades et al, 2014,Bando et al, 1992,Obari et al, 2008,Mori, Inoshita, Takahashi-Fujigasaki et al, 2013). The response to surgery was dramatically different in patients with DG compared to SG growth hormone tumors similar to prior reports (Bakhtiar et al, 2010,Mazal et al, 2001,Kiseljak-Vassiliades et al, 2014).…”
Section: Discussioncontrasting
confidence: 79%
“…The distribution of GH tumors in our series (54.9% SG, 30.4% DG and 14.7% intermediate) was within the range of prior literature, which actually has been quite variable, with DG representing 39-79%, SG 13-35% and intermediate 5-57% of GH subtypes (see Table 2) [18,30,27,31,28,20,29,36,37]. These wide ranges may be attributed to variable subtyping classification systems used, as well as the grouping of DG and intermediate subtypes together, as preferred by some authors [29].…”
Section: Discussionsupporting
confidence: 79%
“…In our analysis, we combined DG and intermediate groups and confirmed that SG tumors more often occur in younger patients compared to DG [27,20,28,30,37]. Several studies reported that SG tumors are more frequently found in female patients [18,29,37,32]; however, in our population, and in agreement with four previous reports, there was no correlation between the gender and GH tumor subtype [28,30,20,31,29]. …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Mori et al examined the pathological features of acromegaly. This study indicates that subclassification based on CK distribution will help to identify clinically aggressive monohormonal GH adenomas but not plurihormonal adenomas (35). In somatotroph adenomas, cases with oncocytic change showed higher percentages of Ki-67 (P = 0.05), but no correlation with extrasellar extension or cytokeratin staining (dot pattern versus perinuclear) was found (36).…”
Section: Pan-ckmentioning
confidence: 98%